INTEGRASI KEBIJAKAN DANA BOS DALAM PENINGKATAN MUTU PENDIDIKAN DASAR DAN DAMPAKNYA TERHADAP KINERJA SEKOLAH SERTA EFISIEN PENGELOLAAN ANGGARAN - Karismayanti Diana Putri; Mahpudin; Yoyo Zakaria Ansori (STKIP Subang, 2025)
This study aims to comprehensively analyze the integration of the School Operational Assistance (BOS) policy in improving the quality of basic education and its impact on school performance as well as the efficiency of education budget management in Indonesia. Employing a descriptive qualitative approach through an extensive literature review, this research synthesizes findings from fifteen national academic journal articles published between 2013 and 2025. The analysis reveals that the BOS policy has made a substantial contribution to enhancing educational facilities, expanding access to education, and strengthening school governance, particularly in aspects of financial transparency and accountability. Nevertheless, the policy’s effectiveness continues to face persistent challenges, including disparities in managerial capacity among schools, delays in fund disbursement, and limited community participation in monitoring and evaluation processes. Furthermore, the synthesis highlights that financial digitalization, the enhancement of school financial literacy, and the integration of data-based monitoring systems are crucial strategies to reinforce both efficiency and sustainability of the BOS program. Therefore, this study recommends that future BOS policy reforms should be more adaptive to technological advancements and local school needs in order to foster an inclusive, efficient, and quality-oriented basic education system.